Simulation of the radiation environment during spent nuclear fuel management - O. V. Balan; S. A. Paskevych; S. S. Pidberezniyy; D. V. Fedorchenko (Ядерна фізика та енергетика)
We have developed a model of the technological process for handling spent nuclear fuel in the reception building of the Centralized Storage Facility for Spent Nuclear Fuel using the ChNPP VRdose Planner Pro v. 2.2DEV-0. The results of the technological process simulation proved the reliability of the virtual models for scenarios of radiation-hazardous work for the optimization of the dose loads of personnel.